The Optimization of the Nasi Bungkus Alms Movement through the Empowerment of Micro, Small, and Medium Enterprises in Cilebut Barat, Sukaraja, Bogor Regency - Suswanto, Budi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This pandemic period, which we have been facing for almost three years, has had various effects in society. One of them is the lack of food. One of the things that can be done is with the rice wrap alms movement. Dividing food for people in need with the help of MSMEs for the provision of food. The purpose of this study is to prove that the opimalization of the Nasi Bungkus alms movement is not only beneficial for people who really need food but can also empower the role of MSMEs. The basis used in the study is Funtional Theory, which explains its functions and uses. This research uses a descriptive qualitative approach that is used to explain and explain the problems of the research subject. Data collection is carried out by summarizing data sources or direct contact with people, events, and situations at the study site. As a conclusion of this study: (1) optimization of the Nasi Bungkus alms movement can be achieved through cooperation with other parties; (2) the Nasi Bungkus alms make the empowerment of MSMEs more optimal. Especially MSMEs engaged in the culinary sector; (2) there is another side, this rice wrap alms movement also fosters strong social solidarity. Where there is one party that has advantages, then it is given to those in need.